The international journal of leadership in public services (Pavilion, 2007)
Draws together international research and lived experiences of leadership to address current issues in the delivery of public services. In addition to containing information and intelligence for chief executives, directors and managers, it also covers topics of interest for public servants working in the health sector, local government, social services, emergency services, public/private sector collaborations and education.